The little data book on information and communication technology. 2011. (Washington World Bank, 2011)
This Little Data Book presents tables for over 213 economies showing the most recent national data on key indicators of information and communications technology (ICT), including access, quality, affordability, efficiency, sustainability, and applications.
Keywords: Digital divide -- Statistics. Information technology -- Economic aspects -- Statistics. Information technology -- Social aspects -- Statistics.v